RANCANG BANGUN SISTEM PENILAIAN ARTIKEL MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) PT POS INDONESIA (PERSERO) - Shinta Amelia (JURNAL ILMIAH INFORMATIKA, 2019)
PT Pos Indonesia is a state-own enterprises that is engage in the postal service. One of it activity is an article writing competition that held once in a three month. Regarding the judgement process of the contest, PT Pos Indonesia currently using manual method which is not effective to determine the rank of each article submitted. Hence, a system is needed to decide the winner of the article writing competition based on criteria that has been determined. To build this system, the author using Weighted Product (WP) in calculating the score of the winner. By using this method, it is expected to help the assessment process to determine the winner of the article writing competition become faster and more effective. From the research conducted, the results of the Weighted Product ranking processing this article assessment have the same value, if the calculation is done with a system that has been build and calculated manually, if it has the same value and weight. From the calculations made, it can be concluded that the three winners of the article competition held by PT Pos Indonesia, with the acquisition of value, PA 11 get value = 0.05144, PA 4 = 0,05074, and PA 5 = 0.05061.